Kegiatan Produksi Benih Rajungan (Portunus pelagicus) Sebagai Upaya Penyediaan Stok di Alam - Nurmini Peniari; Ni Putu Dian Kusuma; Zainal Usman (Lembaga Pengembangan Kinerja Dosen, 2023)
Blue swimming crab (Portunus pelagicus) is one type of crustacean that has great potential to be cultivated. Crab seed production activities are carried out to support the availability of crab seeds so as to reduce fishing activities in nature. Data collection during observation using the survey method, namely by making observations in the field. Seed production activities were carried out since container preparation, preparation of rearing media water, broodstock selection, broodstock rearing, egg hatching, larval rearing, feed management, water quality management, pest and disease management and harvesting. Egg fecundity of 750,000 eggs, egg fertilization rate of 83.60%, egg hatching rate of 76% and larval survival rate of 36.55% were obtained.